Formation of cylindrical micro-lens array on fused silica glass surface using CO2 laser assisted reshaping technique. (December 2015) - Choi, Hun-Kook; Ahsan, Md. Shamim; Yoo, Dongyoon; Sohn, Ik-Bu; Noh, Young-Chul; Kim, Jin-Tae; Jung, Deok; Kim, Jin-Hyeok; Kang, Ho-Min
Abstract: This paper demonstrates the laser assisted formation of plano-convex cylindrical and flat-top curved micro-lens array on fused silica glass surface. Initially, femtosecond laser pulses are irradiated on the sample glass to fabricate periodic linear micro-gratings on the glass surface. Afterwards, we reshape the micro-gratings by several times irradiation of a CO2 laser beam by focusing the laser beam on top of the micro-gratings. As a consequence, plano-convex cylindrical micro-lens array with a period varying from 20 to 40 µm are formed on fused silica glass surface. However, flat-top curved gratings' array is observed on the glass surface for a gratings' period of 50 µm. The fabricated micro-lenses show great consistency in size and shape throughout the sample area. Furthermore, we analyze the formation mechanism of micro-lens array on glass surface using the CO2 laser assisted reshaping technique. The proposed reshaping technique exhibits great potential for forming a large variety of micro-lens arrays on the surface of various transparent materials. Highlights: Fabricated cylindrical micro-lens array (MLA) on fused silica glass using CO2 laser. Plano-convex cylindrical MLA of different period have been reported. Flat-top curved MLA of different period have been reported. Explained the formation mechanism of various MLAs using CO2 laser assisted reshaping technique.